Optimization of Sharia Marketing Strategy in Increasing Customer Interest in Hajj Savings Products at Bank Syariah Indonesia Kc Rantauprapat - Dyah Asti Ningruma; Ahmad Perdana Indra; Tuti Anggraini (UNIVERSITAS PAKUAN, 2025)
This study aims to analyze the effectiveness of sharia marketing strategies in increasing customer interest in Hajj Savings products at Bank Syariah Indonesia (BSI) KC Rantauprapat. This research uses a qualitative approach with descriptive methods. Data were collected through in-depth interviews with marketers and customers, as well as analyzing trends in the number of customers from 2021 to 2024. The results showed that financial transparency and competitive profit-sharing schemes have a significant influence on customer decisions in choosing Hajj Savings. In addition, community-based marketing strategies, such as socialization in community organizations and educational institutions, are proven to increase customer trust and loyalty. Thus, the combination of community-based marketing strategies, financial transparency, product innovation, and service digitalization is a key factor in strengthening the competitiveness of Islamic banking. The implications of this study can be used as a model for optimizing Islamic marketing for other Islamic banks in Indonesia.